Maternal and familial correlates of anthropometric typologies in the nutrition transition of Colombia, 2000-2010 (2018)
Objective: We aimed to assess the maternal and family determinants of four anthropometric typologies at the household level in Colombia for the years 2000, 2005 and 2010. Design: We classified children and lt;5 years old according to height-for-age Z-score ( and lt;-2) and BMI-for-age Z-score ( and gt;2) to assess stunting and overweight/obesity, respectively; mothers were categorized according to BMI to assess underweight ( and lt;18·5 kg/m2) and overweight/obesity (?25·0 kg/m2). At the household level, we established four final anthropometric typologies: normal, underweight, overweight and dual-burden households. Separate polytomous logistic regression models for each of the surveyed years were developed to examine several maternal and familial determinants of the different anthropometric typologies. Setting: National and sub-regional (urban and rural) representative samples from Colombia, South America. Subjects: Drawing on data from three waves of Colombia's Demographic and Health Survey/Encuesta Nacional de Salud (DHS/ENDS), we examined individual and household information from mothers (18-49 years) and their children (birth-5 years). Results Higher parity was associated with an increased likelihood of overweight and dual burden. Higher levels of maternal education were correlated with lower prevalence of overweight, underweight and dual burden of malnutrition in all data collection waves. In 2010, participation in nutrition programmes for children and lt;5 years, being an indigenous household, food purchase decisions by the mother and food security classification were also associated with the four anthropometric typologies. Conclusions: Results suggest that maternal and family correlates of certain anthropometric typologies at the household level may be used to better frame policies aimed at improving social conditions and nutrition outcomes. © The Authors 2018.